Libyan teachers as transitionalist pragmatists: conceptualising a path out of the peacebuilding narrative in conflict-affected contexts (UCL Press, 2023)
The dominant analytical and programmatic frameworks used when writing about conflict-affected contexts such as Libya in Global Northern academia belong to the interdisciplinary field of peace and conflict studies (PACS). Within this, education is increasingly gaining attention as a tool for building peace and developing social justice. This article is a cautious conceptual exploration of how pragmatism might be a timely intervention in the fields of PACS and peacebuilding education. In particular, the article takes a deeper look at the American philosopher John Dewey's pragmatist approach to politics and education, and his conceptualisations of a context-specific 'public', teachers and enquiry for peaceful and democratic living. Throughout, I argue that a pragmatist philosophy is a worthwhile pedagogical project in a challenging context such as Libya, as it is an internal and ground-up discourse, compared to the often externally initiated and top-down discourses of peacebuilding. I speak as an adjacent and connected critic, because I am both a Libyan and a German researching a problem in my country to which I hope to find possible solutions by engaging with discourses and practices in an academic institution in the Global North.